Persepsi Guru terhadap Evaluasi Pembelajaran Tematik dalam Kurikulum 2013 di SDN Paku Jaya 02 Tangerang Selatan - Ina Magdalena; Caesa Nabila; Wulan Hikmah Fratiwi; Nurul Ummah (RC-INSTITUT, 2020)
This study aims to describe teacher perceptions of the evaluation of thematic learning in the 2013 curriculum at SDN Paku Jaya 02 South Tangerang. This study uses a qualitative method. Research subjects are teachers who teach thematic learning. Data collection is done through interviews. The data validity checking technique is triangulation. The steps of data analysis are recording and collecting, reducing, presenting, and verifying. The results of this study indicate that teacher perceptions are positive because teachers carry out evaluations well as evidenced by teachers applying authentic assessments in learning which include assessments of affective, cognitive, and psychomotor aspects.